HMF: Simple Type Inference for First-Class Polymorphism - Leijen, Daan (2007)
HMF is a conservative extension of Hindley-Milner type inference with first-class polymorphism and regular System F types. The system distinguishes itself from other proposals with simple type rules and a very simple type inference algorithm that is just a small extension of the usual Damas-Milner algorithm. Given the relative simplicity and expressive power, we feel that HMF can be a very attractive type system in practice.